Injury reporting in elite ladies Gaelic football and camogie: Perspectives of athlete support personnel - Marese Gilhooly; Róisín Cahalan; Kieran O’Sullivan; Catherine Norton (PLoS ONE, 2025)
Objectives This study investigates athlete support personnel’s (ASP) perspectives on injury reporting among elite ladies’ Gaelic football and camogie players. ASP refers to individuals in coaching, management, and allied health and performance related practice. Methods A mixed-methods design was employed, comprising an online survey and follow-up interviews. Forty-two ASP, currently or recently (within two years) involved in elite ladies’ Gaelic games, completed the survey. Eighteen ASP subsequently participated in semi-structured interviews. Quantitative survey data were analysed using frequency analysis, while interview transcripts were subjected to framework analysis. Results A significant proportion of ASP (43%, n = 18) believe that players do not report all injuries. Most respondents (95%, n = 40) agreed that players often avoid reporting injuries to prevent losing playing time, while 95% (n = 40) cited player fear of being side-lined as a key factor. Furthermore, 93% (n = 39) agreed that players are more likely to report injuries when immediate access to medical personnel, such as team doctors or physiotherapists, is available. Notably, 66% (n = 28) disagreed with the perception that managers view players as weak for reporting injuries, while 19% (n = 8) agreed with this notion. Qualitative findings corroborated these results and identified three overarching themes influencing injury reporting: player factors, system-driven influences, and environmental conditions. Individual factors included a competitive environment that prioritised maintaining team position over health, with experienced players exhibiting greater confidence in reporting injuries compared to younger players, who often perceived management as hierarchical and less approachable. Immediate, consistent access to physiotherapists and other medical professionals was highlighted as a critical enabler of injury reporting. Trust in ASP, built through visible involvement and positive relationships, emerged as a key determinant. Additionally, a supportive team culture that prioritises player well-being alongside performance outcomes was identified as essential for encouraging open injury reporting. Conclusion Injury underreporting is a significant issue among elite ladies’ Gaelic games players, driven by personal, system-level, and environmental factors. Of critical importance for teams and organisations is to provide education for players and ASP on the importance and value of injury reporting to support early and appropriate intervention. Concurrently providing improved medical access will help to foster stronger, trust-based relationships between players and ASP, considered crucial for improving injury reporting practices.